Evaluation of external fish injury caused by hydropower plants based on a novel field‐based protocol. (June 2017) - Mueller, M.; Pander, J.; Geist, J.
Abstract: Knowledge on the extent and mechanisms of fish damage caused by hydropower facilities is important for their ecological improvement. Herein, a novel field‐based fish injury assessment protocol is proposed that includes vitality and four general health criteria, as well as nine lethal and sub‐lethal injury types across 18 body parts. The protocol was validated using 3, 087 specimens from four species of hatchery‐reared fish, as well as 2, 262 specimens from 32 species of wild fish. The protocol allowed a detailed and systematic evaluation of different fish injury types in the field. Injuries related to handling and to contact with different parts of the hydropower structure could be distinguished applying multivariate statistics. This approach allows quantification and comparison of fish injuries across sites, and can help to identify the technologies and operational procedures that minimise damage to fish. It may also be useful to assess fish health in other contexts including aquaculture.